RIGHT TO EDUCATION AS A FACTOR OF EDUCATION PUBLIC ADMINISTRATION IN THE EUROPEAN COURT OF HUMAN RIGHTS PRACTICE - M. Aparov, Andrii; M. Ivanii, Olena; M. Shestopalov, Roman; I. Adashys, Liudmila; V. Morozov, Oleg (Revista Gênero e Interdisciplinaridade, 2020)
The relevance of the issue under study is stipulated by the importance of compliance of the education public administration with the right to education in modern conditions. purpose of the article is to elucidate the right to education as a phenomenon that determines the direction and limits of public administration in the educational sphere. A leading research approach is the systematic analysis of the right to education as a factor in the content and nature of public administration in the educational field. The empirical basis of the study is the European Court of Human Rights practice in the field of the right to education. The article identifies and describes six provisions that characterize the right to education and determine the direction and limits of public administration of education: the obligation of the state to guarantee access to education institutions for persons under the jurisdiction of the state; the state has the discretion to determine the content of education and spread certain philosophical and world outlook ideas through the education. the state is obliged to provide free of charge elementary and general education; the obligation of the state is to ensure equal access of persons to education; the obligation of the state is to develop the school system; to establish the optimal system of scholarships; recognition of a certain degree of autonomy to educational institutions. The material in this article may be useful for scholars exploring the right to education and public administration of education. The main provisions of the study can be used to improve public administration of education, monitor the quality of education, and improve educational legislation.